The coupled effect of surface roughness and nanoparticle size on the heat transfer enhancement of nanofluids for pool boiling - Sharifpur, Mohsen (University of Pretoria, 2022)
Dissertation (MEng (Mechanical Engineering))--University of Pretoria, 2022.